2
$\begingroup$

Say a CES function is that $$Y = A\left[\alpha K^{\rho}+ \beta L^{\rho}\right]^{\frac{1}{\rho}}$$. Clearly this function is constant return to scale whatever the values of $\alpha$ and $\beta$ take.

Then we know that when $\rho=0$, this function goes to the CD case: $Y=AK^\alpha L^\beta$. Now it seems only the case where $\alpha+\beta=1$ satisfies CRS.

What's the intuition of this distinguished result? I am curious because usually in the literature we suppress share parameters and only set say $Y = A\left[K^{\rho}+ L^{\rho}\right]^{\frac{1}{\rho}}$ or $Y=\left[\int_{\Omega}\left(x_{\omega}\right)^{1-\frac{1}{\sigma}} d \omega\right]^{\frac{\sigma}{\sigma-1}}$.


Update 2023/8/15

I am reviewing the question and the answer and find it is a little bit more complicated than my original thought.

The answer by @tdm below uses l'Hôspital to get the limitation, while I now notice that the l'Hôspital law itself presumes that $\alpha + \beta = 1$. So I don't think this is a prove that when you have arbitrary number of $\alpha$ and $\beta$, and when $\rho \rightarrow 0$, you will get a CD production function.

The comment by @walrasian-auctioneer mentions that you can tweak the original production function so that $$Y=A\left[\alpha K^\rho+\beta L^\rho\right]^{\frac{1}{\rho}} = A'\left[\alpha' K^\rho+ \beta' L^\rho\right]^{\frac{1}{\rho}} $$, where $A' = A(\alpha + \beta)^{\frac{1}{\rho}} $, $\alpha' = \frac{\alpha}{\alpha + \beta}$, $\beta' = \frac{\beta}{\alpha + \beta}$, and now $\alpha' + \beta' = 1$. However note that $A'$ is not a constant but also a function of $\rho$, and thus if we put it into limitation $$\lim _{\rho \rightarrow 0} \ln (f(K, L)) = \ln A + \lim _{\rho \rightarrow 0} \left( \frac{\ln (\alpha+\beta)}{\rho} + \frac{ \ln \left(\alpha' K^\rho+\beta' L^\rho\right)}{\rho} \right) $$. The second term in the bracket has been proved as a constant $\alpha'\ln (K)+ \beta' \ln (L)$, however the first term goes to positive or negative infinity if $\alpha + \beta \neq 1$.

As a result, my current conclusion is that while CES is always constant return to scale (CRS) by its definition without any restriction on the value of $\alpha$ and $\beta$, we must have $\alpha + \beta = 1$ to transform the CES function into a CD function in the limitation. Please correct me if I am wrong, and any further intuitive explanations are extremely welcomed.

$\endgroup$
1
  • 1
    $\begingroup$ Since its CRS, just multiply all inputs by $\frac{1}{(\alpha + \beta)}$ and rescale everything, so when you take it to the Cobb-Douglas limit, the fact that exponents sum to 1 always holds. $\endgroup$ May 14, 2022 at 15:19

1 Answer 1

8
$\begingroup$

Consider the function $f(K,L) = [\alpha K^\rho + \beta L^\rho]^{1/\rho}$. We want to evaluate the limit of $f$ when $\rho \to 0$.

$$ \lim_{\rho \to 0} f(K,L) = \lim_{\rho \to 0} [\alpha K^\rho + \beta L^\rho]^{1/\rho} $$ It will turn out to be easier to evaluate $\lim_{\rho \to 0} \ln(f(K,L))$: $$ \lim_{\rho \to 0} \ln(f(K,L)) = \lim_{\rho \to 0} \frac{\ln(\alpha K^\rho + \beta L^\rho)}{\rho} $$ As this evaluates to $\frac{0}{0}$ we use l'Hôspital's rule: $$ \begin{align*} \lim_{\rho \to 0} \ln(f(K,L)) &= \lim_{\rho \to 0} \frac{\alpha K^\rho \ln(K) + \beta L^\rho \ln L}{\alpha K^\rho + \beta L^\rho}\\ & = \frac{\alpha \ln(K) + \beta \ln(L)}{\alpha + \beta}\\ & = \frac{\alpha}{\alpha + \beta} \ln(K) + \frac{\beta}{\alpha + \beta}\ln(L). \end{align*} $$

So taking exponents again gives: $$ \begin{align*} \lim_{\rho \to 0} f(K,L) &= K^{\frac{\alpha}{\alpha + \beta}} L^{\frac{\beta}{\alpha + \beta}} \end{align*} $$ Notice that the factors $\frac{\alpha}{\alpha + \beta}$ and $\frac{\beta}{\alpha + \beta}$ sum to one, which implies CRS.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.